Removal of iron and titanium contaminants from Jordanian Kaolins by using chemical leaching. Issue 3 (4th May 2018) - Gougazeh, M.
ABSTRACT: The present study deals with chemical leaching tests conducted on Batn El-Ghoul kaolin clay deposit, south Jordan. Mineral identification and characterization studies were conducted using X-ray diffraction. The chemical analyses were performed by X-ray fluorescence. The chemical leaching study with sodium dithionite (Na2 S2 O4 ) as leachant was accomplished with the fraction below 44 μm, after classification by screening. The main objective of this study was to evaluate the conditions of chemical leaching for removal of the colouring materials and to improve the brightness. The leaching tests improved the brightness from 56% to 86%. The corresponding iron-oxide removal was in the order of 94%. Removal of 94% iron gives a product containing 0.48% Fe2 O3, which is fit for industrial applications such as fine ceramics and as a filler materials in paper, plastic and rubber industries.